Analysis of Implementation of Steam-Oriented Science Teaching Modules and Profiles of Critical Thinking Skills of Elementary Students - Rahayu, Aprilya Teguh; Widodo, Wahono; Sudibyo, Elok (International Journal of Emerging Research and Review, 2023)
Objectives: This research aims to analyze the profile of students' critical thinking abilities regarding the implementation of STEAM-oriented science and science learning development in elementary schools. Method:  This research is a preliminary study with a data collection technique in the form of a written test by analyzing the data results descriptively and qualitatively. This research was conducted on 7 students consisting of 3 female and 4 male students in elementary school. Results: This research can be concluded that: It was found that the criteria for students' critical thinking abilities were still very low with an average score of 51.76 or a completion percentage of around 36%. In this research, it is hoped that the application of STEAM-oriented learning can improve students' thinking abilities. So, the conclusion is that if students' critical thinking skills are still low, it is necessary to improve students' critical thinking skills, namely by implementing STEAM-oriented learning. Novelty: Development of learning tools oriented to the STEAM approach to improve the science and science critical thinking abilities of elementary school students in the independent curriculum, so that it will improve students' critical thinking skills in line with the demands of the 21st century